Multiomics analysis of a resistant European turnip ECD04 during clubroot infection reveals key hub genes underlying resistance mechanism - Zhou, Xueqing; Zhong, Ting; Wu, Meixiu; Li, Qian; Yu, Wenlin; Gan, Longcai; Xiang, Xianyu; Zhang, Yunyun; Shi, Yaru; Zhou, Yuanwei; Chen, Peng; Zhang, Chunyu (Frontiers in Plant Science, 2024)
The clubroot disease has become a worldwide threat for crucifer crop production, due to its soilborne nature and difficulty to eradicate completely from contaminated field. In this study we used an elite resistant European fodder turnip ECD04 and investigated its resistance mechanism using transcriptome, sRNA-seq, degradome and gene editing. A total of 1751 DEGs were identified from three time points after infection, among which 7 hub genes including XTH23 for cell wall assembly and two CPK28 genes in PTI pathways. On microRNA, we identified 17 DEMs and predicted 15 miRNA-target pairs (DEM-DEG). We validated two pairs (miR395-APS4 and miR160-ARF) by degradome sequencing. We investigated the miR395-APS4 pair by CRISPR-Cas9 mediated gene editing, the result showed that knocking-out APS4 could lead to elevated clubroot resistance in B. napus. In summary, the data acquired on transcriptional response and microRNA as well as target genes provide future direction especially gene candidates for genetic improvement of clubroot resistance on Brassica species.